MENINGKATKAN KETERAMPILAN MENULIS PUISI MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DI KELAS V - Djafar, Regina; Pateda, Lamsike; Pautina, Amalia Rizki (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2024)
Abstract The aim of this research is to find out how to apply the cooperative learning model to improve the poetry writing skills of fifth grade students at Muahammadiyah Elementary School, North City. This type of research is classroom action research with the research subjects being 28 class V students. This research took place in two cycles by applying the PTK research design from Kemmis and McTanggart. Includes: (1) Planning Stage. (2) Implementation of Actions. (3) Observation/observation. (4) Reflection Stage. All of these stages occur in one cycle. This research can be said to have increased if the skill indicators in the Indonesian language poetry subject matter. students who have achieved a minimum completion score of 80 from students with a KKM score of 75. The instruments used are teacher and student observation sheets and skills observation sheets. The skill result in cycle I was 58.4 with a completeness value of 75% so that in cycle I it had not yet reached the completeness value, then continued in the next cycle, namely in cycle II, with a result of 79.0 which had reached the completeness value. So this research has been able to reach the completion value in cycle II Keywords: Cooperative Method; Poetry Writing Skills.